Ultrastructural and cytochemical aspects of the germarium and the vitellarium in Syndesmis patagonica (Platyhelminthes, Rhabdocoela, Umagillidae). (28th January 2014) - Falleni, Alessandra; Lucchesi, Paolo; Ghezzani, Claudio; Brogger, Martín I.
ABSTRACT The cytoarchitecture of the female gonad of the endosymbiont umagillid Syndesmis patagonica has been investigated using electron microscopy and cytochemical techniques. The female gonad consists of paired germaria and vitellaria located behind the pharynx in the mid‐posterior region of the body. Both the germaria and the vitellaria are enveloped by an outer extracellular lamina and an inner sheath of accessory cells which contribute to the extracellular lamina. Oocyte maturation occurs completely during the prophase of the first meiotic division. Oocyte differentiation is characterized by the appearance of chromatoid bodies and the development of endoplasmic reticulum and Golgi complexes. These organelles appear to be involved in the production of round granules, about 2–2.5 μm in diameter, with a homogeneous electron‐dense core surrounded by a granular component and a translucent halo delimited by a membrane. These egg granules migrate to the periphery of mature oocytes, are positive to the cytochemical test for polyphenol detection, are unaffected by protease and have been interpreted as eggshell granules. The mature oocytes also contain a small number of yolk granules, lipid droplets, and glycogen particles scattered throughout the ooplasm. The vitellaria are branched organs composed of vitelline follicles with vitellocytes at different stages of maturation. Developing vitellocytes contain well‐developed rough endoplasmic reticulum and small Golgi complexes involved in the production of eggshell and yolk globules. Eggshell globules are round, measure 4–5 μm in diameter, and have a mosaic‐like patterned content which contains polyphenols. The yolk globules, 2–3 μm in diameter, show a homogeneous protein content of medium electron density, devoid of polyphenols, and completely digested by protease. The mature vitellocytes also contain glycogen as further reserve material. The presence of polyphenolic eggshell granules in the oocytes and of polyphenolic eggshell globules with a mosaic‐like pattern in the vitellocytes have been considered apomorphic features of the Rhabdocoela + Prolecithophora. J. Morphol. 275:703–719, 2014. © 2014 Wiley Periodicals, Inc.